15/#413 Preoperative CT score for predicting complete gross resection at primary and interval debulking surgery of advanced ovarian cancer during the COVID19 pandemic. (4th December 2022) - Eriksson, Ane Gerda; Walberg, Lise; Eyjolfsdottir, Brynhildur; Solheim, Olesya; Skeie-Jensen, Tone; Wang, Yun
Abstract : Objectives: Residual disease at surgery is the most important prognostic factor for women with metastatic ovarian carcinoma (OC). Appropriate patient selection is challenging. Preoperative CT-scores are developed for primary debulking surgery (PDS), however during COVID19 pandemic interval debulking surgery (IDS) has increased. The aim of this single-center pilot-study was to assess the ability to predict complete gross resection (CGR) <1 cm during PDS or IDS based on preoperative CT-scores in women with FIGO st IIIC/IV OC. Methods: All women undergoing PDS or IDS 01/2021–01/2022 were preoperatively scored by a modified MSKCC algorithm including 6 CT criteria. Resectability and residual disease was registered. Results: CT-score was noted in 135 women. 100/135 (74%) underwent surgery: 54 PDS, 46 IDS ( figure 1 ). Patients were deemed inoperable if debulking to ≤1 cm was not feasible, 18/54 (33%) PDS-cases were inoperable. Median CT-score for this group was 4 (range 0–10). Of the remaining 36 PDS-cases, 33/36 (92%) achieved CGR and 3/36 (8%) R>1 cm. Resectability based on CT-score is noted in table 1 . Of the 81 cases triaged to NACT, 38 (47%) never underwent surgery. 36/46 (78%) women undergoing IDS achieved CGR, 2/46 (4%) R>1 cm and 8/46 (17%) were inoperable. Overall, 6 women with CT-scores 1–2 were deemed inoperable. The limiting factor was bowel carcinomatosis for all. Preoperative CT-score of ≤6 and ≤ 4 predicted ≥ 50% CGR at PDS and IDS respectively. Conclusions: When exclusively assessing preoperative imaging, women with initial CT-score >7 should receive NACT or laparoscopic resectability-assessment. Women with CT-score ≤4 after NACT can be offered IDS.